EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2017)
Welcome to the December 2017 issue. During the past seven years, the journal has grown and developed from a little more than an idea, to the formation of the Editorial Board members into what it is today. It is with pride that we are happy to announce that the journal has been accepted to be indexed in the ASEAN Citation Index (ACI).